2020
DOI: 10.1016/j.jcot.2020.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Current controversies in management of fracture neck femur in children: A review

Abstract: Paediatric femur neck fracture is an uncommon injury and is known for high rate of complications. This in turn, can have significant impact on development of hip and overall function of the child. Controversy prevails in many areas of management and it still remains a difficult injury to manage. Through this paper, an attempt has been made to summarize the current concepts in management and suggest current recommendations regarding the controversies so that these injuries can be managed judiciously. A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…ONFH in children is the most common complication following FNF, with a reported incidence of 0–92% in the literature [ 32 ]. Wang et al [ 29 ] reported that age and initial displacement were independent predictors of ONFH in pediatric FNF and insisted that, to avoid ONFH, adequate reduction is more important than the type of reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ONFH in children is the most common complication following FNF, with a reported incidence of 0–92% in the literature [ 32 ]. Wang et al [ 29 ] reported that age and initial displacement were independent predictors of ONFH in pediatric FNF and insisted that, to avoid ONFH, adequate reduction is more important than the type of reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the incidence of coxa vara deformity, LLD, and PPC also showed no differences between the ORIF and CRIF groups. Although these conditions may occur alone or in combination [ 21 , 28 , 32 ], the consensus is that the incidence of coxa vara deformity is related to reduction status, which means that its likelihood could be diminished with anatomical reduction and internal fixation [ 34 , 38 ]. Although our current synthetic results did not reveal the superiority of ORIF over CRIF with respect to complications, theoretically, ORIF is more beneficial than not in treating FNF because it is required to avoid an unacceptable reduction status, which can lead to serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of femoral neck fracture in children is controversial in many aspects [ 14 ]. Due to the rare incidence, there is a scarcity of literature about the management of atraumatic bilateral femoral neck fractures in children.…”
Section: Discussionmentioning
confidence: 99%
“…However, the blood vessels cannot cross the open physis, hence blood supply to the femoral head is critical in children and can be easily disrupted by a fracture. [14][15][16][17] Hence, AVN is the most common and damaging complication of pediatric femoral neck fractures. 18 The risk of AVN depends on several factors, including age, degree of initial displacement of the fracture, time to surgery, and the method of fixation.…”
Section: Discussionmentioning
confidence: 99%